Single-Cell Sequencing Yields Insights in the Evolution of Foot-and-Mouth Disease Virus Persistent Infection - Yuan, Yuncong; Wang, Xingran; Li, Jiadai; Han, Lingling; Du, Hang; Sun, Yidan; Yang, Pu; Zhou, Zhou; Gu, Meijia; Lu, Yang; Shen, Chao (Frontiers in Cellular and Infection Microbiology, 2022)
Foot-and-mouth disease virus (FMDV) could cause acute infection in host cells, or they could coexist with host cells to generate persistent infection. In persistent infection, the virus could survive for a long time in the host and could be transmitted between different host cells. In the case of FMDV-persistent infection cell line, there is a remarkable significant cellular heterogeneity in the FMDV-persistent infection cell line due to differences of viral load in the individual cells within the cell line. However, the mechanisms of FMDV-persistent infection are not well understood. It is now generally accepted that multiple factors contribute to the coevolution of viruses and cells during the course of persistent infection. The outcome would influence the development of persistent FMDV infection conjointly, reaching a state of equilibrium ultimately. Therefore, in order to elucidate the mechanism of cellular heterogeneity in FMDV-persistent infection cell line, single-cell sequencing was performed on BHK-Op, and pseudotime trajectory plot was draw through cell cluster. Based on the cell clusters, we predicted the development and progression of the FMDV-persistent infection. It could be well explained by the fact that, in BHK-Op cells, there are a fraction of infected cells and a fraction of virus-exposed but uninfected bystander cells. By further comparing the transcripts in cell clusters, we found that these genes were involved in changes in ribosome biogenesis, cell cycle, and intracellular signaling including the interferon signaling pathway and mitogen-activated protein kinase (MAPK) signaling pathway. Through comprehensive cross-tabulation analysis of differential expressed genes in various cluster of cells, we identified a high association of Fos, a downstream transcription factor of the MAPK/extracellular signal–regulated kinase (ERK) signaling pathway, with viral replication during the formation of FMDV-persistent infection. Through the further study of Fos, we found that downregulation of Fos facilitates viral clearance during FMDV-persistent infection. Upregulation of c-Raf, which is the upstream of the MAPK/ERK signaling pathway, could promote FMDV replication through downregulation of Fos. Our research is the first to provide insight into the mechanism of the formation FMDV-persistent infection through single-cell sequencing using persistent infection cell line. Pseudotime trajectory analysis was the first time to apply for FMDV-persistent infection cell line. Our work highlights the detailed overview of the evolution of FMDV-persistent infection. We also analyzed the differential expressed genes in the replication or elimination of FMDV within the host. We found that the MAPK/ERK signaling pathway and its downstream transcription factor Fos play an important role in FMDV-persistent infection.